2003
DOI: 10.1095/biolreprod.102.009209
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Prolactin (PRL) and PRL Receptor Messenger RNA in Gilthead Seabream (Sparus aurata) after Treatment with Estradiol-17β1

Abstract: Prolactin (PRL) in fish is considered to be an osmoregulatory hormone, although some studies suggest that it may influence the production of steroid hormones in the gonads. The objective of the present study was to establish if PRL is involved in reproduction of the gilthead seabream-a protandrous hermaphrodite. Adult and juvenile gilthead seabream received implants of estradiol-17beta (E(2)) for 1 wk during the breeding season, and the mRNA expressions of PRL and PRL receptor (sbPRLR) were determined. Norther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
24
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 52 publications
(59 reference statements)
4
24
2
Order By: Relevance
“…found no differences in PRL production during sexual maturation of Japanese eels [79]; however, it is worth noting that these authors measured only the number of PRL-producing cells, which may not reflect the actual levels of circulating PRL. Treatment with oestradiol-17-beta in live seabream produced an increase in PRL mRNA depending on the maturity of the animal [20], an effect similar to the results of Degani et al [26], who found lower levels of PRL mRNA in juvenile male blue gouramis relative to adults, suggesting that PRL may play a role in gonadal development.…”
Section: Reproductive Development and Cyclingsupporting
confidence: 84%
See 1 more Smart Citation
“…found no differences in PRL production during sexual maturation of Japanese eels [79]; however, it is worth noting that these authors measured only the number of PRL-producing cells, which may not reflect the actual levels of circulating PRL. Treatment with oestradiol-17-beta in live seabream produced an increase in PRL mRNA depending on the maturity of the animal [20], an effect similar to the results of Degani et al [26], who found lower levels of PRL mRNA in juvenile male blue gouramis relative to adults, suggesting that PRL may play a role in gonadal development.…”
Section: Reproductive Development and Cyclingsupporting
confidence: 84%
“…Firstly, PRLR mRNA and mature protein have been found in the gonads of a number of fish species, including Mozambique tilapia [31], Nile tilapia [91], seabream [20,95], Japanese flounder [41], goldfish [113], fugu (Takifugu rubripes) [59], and starry flounder [72], suggesting that PRL may be involved in spermatogenesis, vitellogenesis, and/or ovulation. Further studies involving immunohistochemical analyses of fish gonads across the full reproductive cycle are required to clarify these functions.…”
Section: Reproductive Development and Cyclingmentioning
confidence: 99%
“…In the gonad of adult gilthead seabream, the transcript level of PRLR, which is a PRLR2 according to the phylogenetic analysis (Fig. 5), increased significantly (50-fold) after E 2 treatment, but a 24-fold decrease was found in the juvenile gonad (Cavaco et al 2003). However, in mammals, E 2 stimulates the expression of PRLR in various tissues (Cheng et al 1984, Tsim et al 1985, Barash et al 1992, Cassy et al 2000.…”
Section: Figurementioning
confidence: 96%
“…The results of the promoter studies were in generalIntroduction Prolactin (PRL) is recognized as the most versatile pituitary hormone among diverse species (Manzon 2002). In fish, various physiological functions have been attributed to PRL, such as enhancement of immune functions (Harris & Bird 2000), pigment dispersion in the tegumentary chromatophores (Kitta et al 1993), synergism with production of steroid hormones in the gonads (de Ruiter et al 1986), and reproduction (Cavaco et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Prolactin (PRL) regulates several important physiological processes in fish, including salinity adaptation (Manzon, 2002;Sakamoto and McCormick, 2006), modulation of immune functions (Harris and Bird, 2000), pigment dispersion (Kitta et al, 1993), reproduction (Cavaco et al, 2003) and development (Nguyen et al, 2008). In euryhaline species, such as tilapia, PRL is known to promote freshwater adaptation.…”
Section: Introductionmentioning
confidence: 99%